Measuring Informal Employment in the framework of the Continuous Household Survey (ECH) 2012 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
This test is performed in order to measure informal employment in Nicaragua from the Continuous Household Survey IV quarter 2012 the National Institute for Development Information (INIDE). Data processing focused on quantitative and qualitative methods, where for economic, area of residence, education, marital status and activity, allowing knowing the level of informal employment focused on the different categories (explanatory variables) and through this document analyzed. And also possible to measure informal employment. The results of processing variables have shown that informal employment has prevailed in the analyzed variables, ie the variables analyzed is characterized that the level of employment are in the informal sector because that have limitations such as not enough jobs and are not enrolled in the insurance. In conclusion of all the research allowed to appreciate and to ascertain the level of people who are in the informal sector (Informal Employment), and industry (Informal Economy). Using the possible methods that allowed for our research
Keywords: Total Population; Continuous Household Survey; Informality; Employment